A Modern Approach to the Nature and Trading Mechanism of Forward and Futures Contracts - Asif Ehsan, Muhammad (IJRDO - Journal of Business Management, 2017)
Forward and futures contracts have been designed to provide protection forparticipants in financial markets against adverse movements in the prices of the underlying assets. These contracts allow producers and commercial operators to fixthe price of commodities wherein they trade in advance of making or taking physicaldelivery. The paper accentuates that forward and futures contracts have pedantically changed the face of finance by creating new ways to understand, measure and managevarious kinds of risk. Hence these contracts are considered an integral part of anyfirm’s risk management strategy in order to ensure that value enhancing investmentopportunities are properly pursued. The paper also canvasses several scathingcriticisms of forward and futures contracts which tend to ratiocinate that thesecontracts are a flagrant cause of destabilization, volatility, and oscillation in financialmarkets. It is globally observed that hardly one or two per cent of traded contracts aresettled by actual delivery of the underlying assets, whereas the rest of the contracts aremerely used to promote speculative activities in the markets